Assessment of Birth Weight and Its Related Factors among Infants Born in the Hospitals of Ahwaz Jondishapour University - Shiva Faghih; ehsan hejazi (Shiraz University of Medical Sciences, 2014)
Background: Given the importance of birth weight and the effects of anthropometric indices and socioeconomic status on it, this study was conducted to assess birth weight and its related factors among infants born in the hospitals of Ahwaz Jondishapour University. Methods: This cross-sectional study was carried out on 269 newly born babies and their mothers in hospitals of Ahwaz Jondishapour University during 2009. Neonate anthropometric measures were obtained from hospital reports. The mothers were asked about their weight before pregnancy, their weight gain and demographic and socioeconomic data. SPSS software version16 was used to analyze the data. Relationships among infants and mothers' anthropometric indices were assessed using bivariate correlation. Results: 86.8% of the infants were normal as to weight, 8.7% were underweight, and 4.5% overweight. Mothers' weight gain during pregnancy and BMI before pregnancy were 12.18±5.18(kg) and 24.75±4.78(kg/m2), respectively. There was a significant correlation between infant's birth weight and mother's weight, height and weight gain during pregnancy. Discussion: Results of this study showed that mothers' weight before pregnancy and their pregnancy weight gain have a key role in infant birth weight, so controlling the mother's weight gain according to recommendation has a great effect on infant's health.